Essentially Infinite-Dimensional Evolution Equations - Mal'tsev, A. Yu. (Ukrains’kyi Matematychnyi Zhurnal, 2004)
We investigate the Cauchy problem for evolution equations with essentially infinite-dimensional elliptic operators.